Issues in Text and Translation Technique in the Gamma-Gamma Section of 3 Reigns (1 Kings) - Turkanik, Andrzej Szymon (Tyndale bulletin, 2004)
A dissertation contributing to the study of the transmission history of the Samuel-Kings corpus, examining the translation technique employed in the gamma-gamma section of 3 Reigns (1 Kgs 2:12–21:43).